Does war enhance or undermine other-regarding preferences and trust? - Stein Terje Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
Our study investigates how the devastating 2020-2022 Tigray War has affected the social preferences, reciprocity norms, and trust in a large sample of rural young adults in Tigray, Ethiopia, belonging to rural business groups. We rely on field experimental data with standardized incentivized experiments conducted in 2019 and 2023 to categorize subjects into social preference types. We also identify reciprocity norms, generosity, trustworthiness, and trust in in-group and out-group conditions for a large balanced sample (N=1939). The in-group framing is for subjects belonging to the same business group (N=238 business groups). The out-group is an unknown person from another business group in the same district. Overall, the war in Tigray has resulted in an erosion of within-community social capital. This erosion of social capital includes weakened reciprocity norms, a reduction in the share of the population that behaves altruistically or egalitarian, and a reduction in generosity, trustworthiness, and trust (reduction of 0.6-0.75 Cohen's d units) that is strongest among those who behaved altruistically or egalitarian before the war. The same and similar effect sizes are also prevalent within business groups, but within business groups, social capital remains high compared to generalized social capital in the study areas. To a small extent, we find that differential exposure to violence or other war incidents among subjects explains the fairly large changes in social capital that our experiments revealed. This may imply that the war spillover effects overshadow the effects of individual war exposure.
hdl:11250/3163657
Keywords: C93; D74; D84; D91; O12; 330; War impacts; Social preferences; Reciprocity norms; Trust; Fieldexperiment; Rural business groups; Ethiopia